ANALYSIS OF NEWS COVERAGE ANALYSIS OF NEWS COVERAGE OF KASHMIR CRISIS BY GLOBAL NEWS CHANNELS : ANALYSIS OF NEWS COVERAGE OF KASHMIR CRISIS BY GLOBAL NEWS CHANNELS AFTER THE ABOLITION OF ARTICLE 370 - Ahmad, Taufiq (Journal of Peace, Development and Communication, 2021)
This study analyzes the Kashmir conflict by little empirical work on Kashmir News after the abolition of Article 370. The purpose here is to identify the nature of news coverage by the global news media. For this purpose, 193 new stories were selected which were appeared at the web sources of three global news channels BBC, CNN, Aljazeera. This study primarily focusses on Content analysis of how CNN, BBC and AL JAZEERA designed Kashmir in their online news broadcasting with time frame of from 5 August to 30 September 2019 soon after the revocation of Article 370 while determining the difference in storytelling and the search for stories of information about Kashmir. By using an original coding program that extract on the coverage of Kashmir conflict, media effects and agenda-setting theories, the analysis is found that AL JAZEERA has heavily relied on episodic coverage and focued on international condemnation frame in its coverage than CNN which heavily focused on the Human-interest frame as well as BBC relied on the responsibility frame in its coverage related Kashmir. The study investigates the sources of the stories where AL JAZEERA cited government leader and official statements; CNN added journalists’ views whereas BBC heavily relied on their correspondents’ version. However, the investigation provides the insight into the worldwide media coverage of the issue and their views. Key words. Kashmir, Global media, News coverage, framing, article 370, CNN, BBC, Aljazeera